The spatial pattern of voter choice homogeneity in the Nigerian presidential elections in the fourth republic - Nwankwo, Cletus Famous (Bulletin of Geography. Socio-economic Series, 2019)
The return of democratic rule in 1999 after many years of military intervention has left some electoral geographic imprints on Nigeria: voting pattern has varied over this period. A spatial analysis of voter choice homogeneity in the Nigerian presidential election from 1999 to 2015 was done to unravel the striking pattern of voting that is often obscured when only votes received by parties that won the elections are considered. The analysis shows that voting patterns have structured Nigeria’s electoral landscape from a random to clustered but dissected then to a clustered but regionalised milieu of a nation of two voting worlds sharply depicting the ethno-religious divide of the country. While, economic, security and governance issues shape voting behaviour they only become weighty when comingled with ethno-religious and regional sentiments.